Studies directed towards the total synthesis of polyether antibiotic ionomycin: asymmetric synthesis of fragments C(24)–C(32) and C(1)–C(23). Issue 40 (7th October 2015) - Yadav, J.S.; Yadav, Nagendra Nath; Reddy, B.V. Subba
Abstract: A convergent and stereoselective approach for the synthesis of C1–C23 and C24–C32 segments of polyether antibiotic, ionomycin has been achieved. The key steps involved in this approach are the elaboration of two advanced fragments from a common precursor using enzymatic desymmetrization to create two methyl chiral centers, desymmetrization of the bicyclic olefin to introduce two methyl and two hydroxyl chiral centers, the use of Evans auxiliary to introduce another methyl group and the creation of four chiral centers in bis -tetrahydrofuran ring by Sharpless asymmetric epoxidation and the regioselective opening of epoxide with methyl sulphone. The coupling of C11–C16 with C17–C23 was achieved through a Julia-Kocienski olefination and directed Aldol reaction. Oxidation of C9 alcohol facilitates the coupling of C10–C23 with C1–C9. Graphical abstract: